100 best letters, 1847-1947 - Sharma, H. D. (Hari Dev) (New Delhi : HarperCollins Publishers India, 2000)
Collection of letters predominantly on India during British rule.
Includes index.
Bibliography: p. 433-440.
Keywords: India -- History -- British occupation, 1765-1947 -- Sources